Lohengrin [romantic opera in three acts] - Wagner, Richard 1813-1883
"With powerful conviction, Nikolaus Lehnhoff interprets Wagner's Lohengrin as the dramatic struggle of masculine and feminine, revenge and compassion. Powerfully acted, almost like a Strindberg play, and musically of the highest order, this Lohengrin from the Festspielhaus Baden-Baden will be a benchmark production for decades."--Container.
Interpr.: Klaus Florian Vogt [Lohengrin]. Solveig Kringelborn [Elsa von Brabant]. Hans-Peter König [Heinrich der Vogler]. Waltrud Meier [Ortrud]. Tom Fox [Telramund]. Roman Trekel [Heerufer]. EuropaChorAkademie Mainz. Chorus of the Opéra National de Lyon. Deutsches Symphonie-Orchester Berlin. Kent Nagano [Dir.]. Nikolaus Lehnhoff [Bühnenegie]. Thomas Grimm [Filmregie]. - Live-Aufn.: Baden-Baden, Festspielhaus, 1., 3. und 5. Juni 2006. - Enth. Bonus-Material. - Gesungen in dt. Sprache. - Text des Beih.: engl., franz., dt. - Untertitel: engl., franz., dt., span. und ital.
Keywords: Operas; Film; Opera - Performance